Guilty Feeling Narapidana Kategori Residivis Studi Kasus di Lembaga Pemasyarakatan Kelas II A Banjarmasin - Maghfirah, Wafa Yuzayyina; Mulyani, Mulyani; Fadhila, Mahdia (Islamic Psychology Study Program, Faculty of Ushluddin and Humanities, UIN Antasari Banj, 2021)
The tendency to improve themselves and the mistakes that have been made are indicators of the guilty feeling, feelings of guilt can arise in anyone, even a recidivist. This study aims to see the dynamics of feelings of guilt in recidivist prisoners, and describe the types and factors that influence it. This research is a case study cualitative research, conducted at the Correctional Institution Class II A Banjarmasin with the subject of 2 recidivists. The data test method used was a screening test with a guilt and shame proneness scale (GASP), interviews and observations. The result this study indicate that those who assesss regret are different from before, there is a perception of disappointment and burdens to the closest people, motivated to become a better person. Feeling guilty about breaking the legal guilt. Basides that he realizes and understands the lack of religious knowledge that violates the stipulated provisions and feels guilty. The factors underlying the guilt feeling of the two subjects are internal and external factors